Interactive effects of body mass index and physical activity on sleep quality in nursing students - Li, Guangjian; Wu, Mengying; Lu, Guo; Yu, Zijun; Bao, Zhigang; Yu, Chengying; Shu, Jingping; Zhu, Jinmei; Sun, Xugui (Frontiers in Psychiatry, 2025)
BackgroundSleep problems are highly prevalent among nursing students, who often experience academic stress, irregular schedules, and heavy clinical training, which may negatively affect their physical and mental health as well as learning outcomes. Body mass index (BMI) and physical activity are recognized as important factors associated with sleep quality, but their combined effects in nursing students remain insufficiently explored. This study examined the effects of BMI and physical activity on sleep quality in nursing students and explored their interaction, aiming to improve this population’s lifestyle and sleep health.MethodsA cross-sectional study was conducted on 1,746 nursing students from six universities in Anhui and Jiangsu provinces, China. Data were collected using a general information questionnaire, the Self-Rating Scale of Sleep (SRSS), the Physical Activity Rating Scale (PARS-3), and BMI measurements. Logistic regression models were employed to identify influencing factors and analyze the interaction between BMI and physical activity.ResultsThe positive screening rate for sleep disorders in nursing students was 38.1%. Logistic regression analysis showed that internship experience (OR = 1.282, 95% confidential interval, or CI: 1.003–1.639) and low-intensity physical activity (OR = 5.820, 95% CI: 3.408–9.942) were risk factors for sleep disorders. Conversely, being underweight or normal weight (OR = 0.456, 95% CI: 0.303–0.687) and overweight (OR = 0.436, 95% CI: 0.269–0.704) were protective factors. Interaction analysis revealed significant multiplicative interactions between overweight and engagement in moderate-to-high intensity physical activity (OR = 6.582, 95% CI:1.670–25.943) and between obesity and engagement in moderate-to-high intensity physical activity (OR = 6.231, 95% CI:1.518–25.575). While additive interaction indicators did not reach statistical significance, a synergistic trend was observed.ConclusionThe prevalence of sleep disorders in nursing students is relatively high. BMI and physical activity interact and are both significant influencing factors. Thus, comprehensive interventions targeting BMI and physical activity should be emphasized in nursing students’ health management to improve their sleep quality and overall well-being.